pH induced stress enhances lipid accumulation in microalgae grown under mixotrophic and autotrophic condition - Alkhamis, Yousef Ahmed; Mathew, Roshmon Thomas; Nagarajan, Ganesan; Rahman, Sheikh Mustafizur; Rahman, Md. Moshiur (Frontiers in Energy Research, 2022)
Production of biodiesel together with wastewater treatment and CO2 sequestration is a promising technology. The growing levels of carbon dioxide in the atmosphere increase the amount of dissolved CO2 in natural watercourses, triggering the increase in concentrations of bicarbonate and hydrogen ions while dropping those of carbonate and hydroxyl ions. The active carbon cycling in coastal areas, which can result in periodic and daily fluctuations in pH and CO2 concentrations that may surpass those anticipated for the extensive marine ecosystems, is regarded as one of the consequences of climate change. Studies were conducted to examine the effects of various pH levels on algal growth and lipid production in order to better understand how the growth of algae may be influenced in such conditions. In the present study, the influence of three different pH levels (6, 8, and 10) was studied to evaluate microalgae’s carbohydrate utilisation and lipid accumulation during the operation’s starvation phase (SP). Microalgae, in the study, were cultivated in two modes, namely mixotrophic [growth phase (GP)] and autotrophic [pH-induced (SP)] conditions. Enhancement in biomass formation, and intracellular carbohydrate accumulation were recorded during the GP operation, while noticeable lipid productivities (Total/neutral, 26.93/10.3%) were observed during SP operation at pH 8. Pigment analysis showed variations in both the procedures where higher Chl a concentration was noticed in GP, and higher Chl b was detected during SP. Nile red fluorescent staining strongly supports the existence of intracellular lipid bodies (LB). GC analysis of fatty acid methyl esters (FAME) showed the existence of a substantial amount of saturated fatty acids (SFA) compared with unsaturated fatty acids (USFA). Efficient wastewater treatment with nutrient assimilation was reported during the GP operation, demonstrating the phyco-remediation.